Indexes of structural reform in Latin America - Morley, Samuel A. (UN. ECLAC SantiagoCL, 1999)
Attempts to quantify the process of structural reform in Latin America in five areas: trade reform, financial liberalization, tax reform, liberalization of external capital transactions and privatization. Presents indexes for these five areas for 17 countries for the period 1970-1995.